High-efficiency electroluminescence and amplified spontaneous emission from a thermally activated delayed fluorescent near-infrared emitter - Dae-Hyeon, Kim; Anthony D’Aléo; Xian-Kai Chen; Atula D S Sandanayaka; Yao, Dandan; Zhao, Li; Komino, Takeshi; Zaborova, Elena; Canard, Gabriel; Tsuchiya, Youichi; Choi, Eunyoung; Jeong Weon Wu; et al. (Nature photonics, 2018)
Near-infrared organic light-emitting diodes and semiconductor lasers could benefit a variety of applications including night-vision displays, sensors and information-secured displays. Organic dyes can generate electroluminescence efficiently at visible wavelengths, but organic light-emitting diodes are still underperforming in the near-infrared region. Here, we report thermally activated delayed fluorescent organic light-emitting diodes that operate at near-infrared wavelengths with a maximum external quantum efficiency of nearly 10% using a boron difluoride curcuminoid derivative. As well as an effective upconversion from triplet to singlet excited states due to the non-adiabatic coupling effect, this donor–acceptor–donor compound also exhibits efficient amplified spontaneous emission. By controlling the polarity of the active medium, the maximum emission wavelength of the electroluminescence spectrum can be tuned from 700 to 780 nm. This study represents an important advance in near-infrared organic light-emitting diodes and the design of alternative molecular architectures for photonic applications based on thermally activated delayed fluorescence.